Red blood cell-derived semaphorin 7A promotes thrombo-inflammation in myocardial ischemia-reperfusion injury through platelet GPIb - David Köhler (Nature Portfolio, 2020)
Reperfusion injury following myocardial ischemia is aggravated by inflammation and platelet–neutrophil complex formation. Here the authors show that semaphorin 7A binds to platelet GPIb, enhancing platelet–neutrophil interaction and increasing post-ischemic myocardial tissue injury, and that blockage of semaphorin 7A is protective.